2022
DOI: 10.1186/s12889-022-14023-w
|View full text |Cite
|
Sign up to set email alerts
|

Chronic diseases and multi-morbidity in persons experiencing homelessness: results from a cross-sectional study conducted at three humanitarian clinics in Germany in 2020

Abstract: Background Persons experiencing homelessness (PEH) suffer a high burden of chronic diseases and multi-morbidity, yet face significant barriers in accessing healthcare services. These health inequalities were further aggravated during the COVID-19 pandemic. While there is a lack of comprehensive health data on PEH, even less is known about populations experiencing housing exclusion, a hidden form of homelessness. This study examines and compares chronic diseases and multi-morbidity in PEH, perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Our study suggests that long COVID may exacerbate existing challenges that PEH face in health and wellbeing [ 48 50 ]. Persistent COVID-19 symptoms impacted participants’ key activities such as employment, ability to care for themselves and others, and access to homelessness services.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that long COVID may exacerbate existing challenges that PEH face in health and wellbeing [ 48 50 ]. Persistent COVID-19 symptoms impacted participants’ key activities such as employment, ability to care for themselves and others, and access to homelessness services.…”
Section: Discussionmentioning
confidence: 99%
“…This may have facilitated the spread of the virus (8). In addition to these environmental risk factors, people who are homeless are known to have a high prevalence of chronic diseases, particularly lung disease, addictions, and are predominantly male and aging, which are known risk factors for severe forms of COVID-19 (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, previous studies showed that the spread of COVID-19 was greater in the population experiencing homelessness than in the general population, with seroprevalence rates ranging from 4 to 36%, depending on where they were living at the time of the screening/diagnosis (i.e., rates at least 3-4 times higher than in the general population) (12)(13)(14)(15)(16)(17)(18)(19)(20). Nonetheless, few studies have investigated the consequences of the COVID-19 pandemic on the health status of people experiencing homelessness, either in terms of morbidity or mortality (9,(21)(22)(23)(24). Most of these studies have limited their design to a cross-sectional approach, with the results mainly related to the first wave of the pandemic (from March to August 2020).…”
Section: Introductionmentioning
confidence: 99%